Fundamentals Of Entreprenurship (ENT300) Business Plan ZMS Hipster Pomade Enterprise / Muhamad Zubair Mad Sam - Mad Sam, Muhamad Zubair (2020)
ZMS Hipster Pomade Enterprise offers pomade product to syle hair for customer,provide variety of pomade like apple,vanilla and mix berries with good quality and affordable price. Our company more focusing kedah as market potential because that was the owner place which is easy to get customer to buy the product.In addition, customer can reach the company easily to complain or give feedback about our product. Target market for our business pomade is male.It because our product is made for male either kids,teenager or old man that interested to sytle their hair. ZMS Hipster Pomade competitive advantages are long lasting product which can use up to 12 hours when use it. Next is pomade that our company is made is from fruit ingredients with a good smells that made this product special rather than other product. Moreover,our pomade is affordable price which is cheap than other top brand that cannot afford by customer with lower income,but with our pomade they can get product high quality with low price.